2006
DOI: 10.1016/j.brainres.2006.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal midazolam regulates spinal AMPA receptor expression and function after nerve injury in rats

Abstract: Spinal γ-aminobutyric acid (GABA) and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors have been implicated in the mechanisms of neuropathic pain after nerve injury; however, how these two receptors interact at the spinal level remains unclear. Here we show that intrathecal midazolam through activation of spinal GABAA receptors attenuated the expression and function of spinal AMPA receptors in rats following peripheral nerve injury. Thermal hyperalgesia and mechanical allodynia induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
2
23
0
4
Order By: Relevance
“…25 In our study, intrathecal application of midazolam failed to evoke any significant changes in nociceptive thresholds except in the P21 group, in which thresholds were decreased. However, most studies showing an ability of midazolam to reduce pain behaviors or to reduce dorsal horn excitation are performed in models of neuropathic or inflammatory pain 24,26 or in isolated spinal cord slices, 23 whereas intrathecal midazolam has no effect on basal sensory thresholds in sham adult animals, 24,26 in general agreement with our findings. The differences in effect of midazolam in whole animals and in isolated tissue indicate that the ability of the drug to modulate sensory thresholds is dependent on intact descending inputs from supraspinal sites.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…25 In our study, intrathecal application of midazolam failed to evoke any significant changes in nociceptive thresholds except in the P21 group, in which thresholds were decreased. However, most studies showing an ability of midazolam to reduce pain behaviors or to reduce dorsal horn excitation are performed in models of neuropathic or inflammatory pain 24,26 or in isolated spinal cord slices, 23 whereas intrathecal midazolam has no effect on basal sensory thresholds in sham adult animals, 24,26 in general agreement with our findings. The differences in effect of midazolam in whole animals and in isolated tissue indicate that the ability of the drug to modulate sensory thresholds is dependent on intact descending inputs from supraspinal sites.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that, in the adult, intrathecal midazolam decreases dorsal horn excitation and increases nociceptive thresholds via a reduction in ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor expression. 23,24 GABA A receptors are present both in intrinsic dorsal horn neurones and on primary afferent fibers. We must therefore acknowledge the possibility that the actions of midazolam may be being mediated by a presynaptic action of the drug potentiating inhibition of excitatory sensory input to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal administration of the GABA-A receptor agonists, muscimol and isoguvacine, attenuate behavioral allodynia and hyperalgesia after nerve injury [19]. The effect of midazolam on the GABAergic system might make it effective in alleviating neuropathic pain [7,20,21]. Koninen and Dickenson [7] demonstrated that midazolam reduced A-delta and C-fiber-evoked activity and reversed cold and mechanical allodynia after spinal nerve ligation.…”
Section: Discussionmentioning
confidence: 97%
“…After formalin injection in the whisker pad of rats, the number of cells immunoreactive for GluA1 and GluA2/3 was found to be reduced in the superficial medullary DH [281]. In the spinal nerve ligation and chronic constriction injury models of neuropathic pain, spinal upregulation of GluA1-3 subunits in the DH has been reported [223,[282][283][284] (but see [277]), while spinal nerve transection was observed to result in enhanced transcription of GluA3 and GluA4 in the dorsal spinal cord [285].…”
Section: Amparsmentioning
confidence: 90%